2021
DOI: 10.1016/j.jmbbm.2020.104126
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal plasma treatment of polymers modulates biological fouling but can cause material embrittlement

Abstract: Plasma-based treatment is a prevalent strategy to alter biological response and enhance biomaterial coating quality at the surfaces of biomedical devices and implants, especially polymeric materials. Plasma, an ionized gas, is often thought to have negligible effects on the bulk properties of prosthetic substrates given that it alters the surface chemistry on only the outermost few nanometers of material. However, no studies to date have systematically explored the effects of plasma exposure on both the surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Deconvolutions of high-resolution C1s scans suggested that most engrafted oxygen was incorporated as hydroxyl groups, with lesser amounts as ketones/aldehydes and carboxyls/esters, for all tested plasma durations. This finding is in agreement with previous reports [17,37]. However, the abundance of hydroxyl groups leveled off after 10 min of treatment, as existing hydroxyls were oxidized further to species such as ketones, carboxylic acids, or possibly even carbonates [38,39,41].…”
Section: Effects Of Plasma Treatment On Pp Substrate Wettability and supporting
confidence: 93%
See 3 more Smart Citations
“…Deconvolutions of high-resolution C1s scans suggested that most engrafted oxygen was incorporated as hydroxyl groups, with lesser amounts as ketones/aldehydes and carboxyls/esters, for all tested plasma durations. This finding is in agreement with previous reports [17,37]. However, the abundance of hydroxyl groups leveled off after 10 min of treatment, as existing hydroxyls were oxidized further to species such as ketones, carboxylic acids, or possibly even carbonates [38,39,41].…”
Section: Effects Of Plasma Treatment On Pp Substrate Wettability and supporting
confidence: 93%
“…The former strategy represents a greener chemistry process, and eliminates the risk for residual hazardous compounds, which is especially important for any materials that may ultimately come into contact (directly or indirectly) with human cells or tissues (e.g., medical devices, water treatment filters/membranes). Furthermore, appropriate selection of plasma treatment parameters can ensure minimal impact on bulk mechanical properties of load-bearing substrates [17]. Apart from CD-based coatings, findings herein support the use of substrate plasma activation for improving uniformity and adherence of adhesives or paints (especially polyurethane-based formulations) upon low surface energy substrates such as polyolefins.…”
Section: Effects Of Plasma Treatment On Pcd Coating Uniformity Adhermentioning
confidence: 57%
See 2 more Smart Citations
“…Bacterial adhesion decreased after 1 min of plasma treatment (p > 0.048) whereas after 10 min and 20 min of plasma treatment, the bacterial attachment rate, in comparison with the 1-min rate, was reduced by half (p < 0.001). These results imply that the time exposure of a surface to plasma treatments affects its chemical properties and behavior towards microorganisms (Gd et al 2020). Furthermore, Lin et al (2020) elaborated effective antiadhesive coatings towards Escherichia coli.…”
Section: Cold Plasma Treatments Of Materials For Preventing Bacterial Adhesionmentioning
confidence: 81%